Family and Family Values on the Basis of Lithuanian and Polish Tatar Manuscripts - Miškinienė, Galina (Vilnius University Open Series, 2021)
Family always was among the most important human values. Family subject became essential part of the ethnolinguistic researches. Child birth, wedding, death and funeral is the cycle of life, particularly tightly related to traditional culture. Description of family rituals and traditions highlights family relationships which is the basis of this paper. Kinship subject constantly found in stories about ethnic religiosity, rites of folk medicine, myths and legends. In her article I. A. Sedakova has noted that “any discussion on the topic of kinship has sufficiently relevant data for complex linguistic research” (Sedakova, 2009, 226).The comprehension of family and its values are reflected in a completely different way in Lithuanian Tatar manuscripts written in Slavic languages and Arabic characters. Emigrants from Golden Horde and Crimean khanate were the one of the first muslims to settle in Grand Duchy of Lithuania in 14th century. Three most important events in human life: birth, wedding, death and accompanying rites used by Lithuanian Tatars are different from the ones used by local residents. In general Lithuanian Tatar rites have common Muslim roots, even though they have traces of shamanism and perceptible influence from Christianity. One can talk about religious syncretism when the various teachings of faith and cult rites are combined in the interplay of religions and their historical development. In this article we try to reveal the whole network of connections and relationships that contain the concepts of family and family values, based on texts written in Lithuanian Tatar manuscripts in Slavic languages (Ruthenian and Polish).
Keywords: family; family values; Lithuanian Tatar manuscripts; text